Developing Social Intelligence in Leadership: a Vehicle for Promoting Peaceful Leadership-Followership Interactions in Nigerian Universities (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The social intelligence/skills of the leadership of the university system and other organizations generally, is very critical to developing and maintaining a peaceful workplace relationship and enhancing leadership success. This work therefore, focused on developing social intelligence in leadership: A vehicle for promoting peaceful leadership-followership interactions in Nigerian universities. The work explored and extensively discussed the concept of social intelligence as perceived by different scholars. It also identified the characteristics of a socially intelligent leader/individual. Further highlighted and explicated were the different techniques/instruments that can be employed in measuring the social intelligence of a leader. Also examined herein were the strategies for developing and improving social intelligence in leadership as well as the importance of social intelligence in leadership. Finally, conclusion was also made.